2010
DOI: 10.1007/978-3-642-15643-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Promptness in ω-Regular Automata

Abstract: Abstract. Liveness properties of on-going reactive systems assert that something good will happen eventually. In satisfying liveness properties, there is no bound on the "wait time", namely the time that may elapse until an eventuality is fulfilled. The traditional "unbounded" semantics of liveness properties nicely corresponds to the classical semantics of automata on infinite objects. Indeed, acceptance is defined with respect to the set of states the run visits infinitely often, with no bound on the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…On the other hand, in many applications, it is important to bound the wait time. In the last decade, many papers have focused on quantitative aspects, in particular boundedness requirements, of formal verification [1,19,10], including parity games [10,15,23,24]. In [19], the authors introduce Prompt LTL, an extension of standard LTL [25] with the prompt-eventually operator F p : a finite system satisfies a Prompt LTL formula ϕ iff there is a bound on the wait time for all the prompt-eventually subformulas of ϕ in all the computations of the system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in many applications, it is important to bound the wait time. In the last decade, many papers have focused on quantitative aspects, in particular boundedness requirements, of formal verification [1,19,10], including parity games [10,15,23,24]. In [19], the authors introduce Prompt LTL, an extension of standard LTL [25] with the prompt-eventually operator F p : a finite system satisfies a Prompt LTL formula ϕ iff there is a bound on the wait time for all the prompt-eventually subformulas of ϕ in all the computations of the system.…”
Section: Introductionmentioning
confidence: 99%
“…In [19], the authors introduce Prompt LTL, an extension of standard LTL [25] with the prompt-eventually operator F p : a finite system satisfies a Prompt LTL formula ϕ iff there is a bound on the wait time for all the prompt-eventually subformulas of ϕ in all the computations of the system. The automata-theoretic counterpart of the F p operator has been investigated in [1]. Parity games extended with promptness requirements, the so-called finitary parity games, have been studied in [10].…”
Section: Introductionmentioning
confidence: 99%
“…In [19], it has been addressed by forcing Ltl to express "prompt" requirements, by means of a prompt operator F p added to the logic. In [1] the automata-theoretic counterpart of the F p operator has been studied. In particular, prompt-Büchi automata are introduced and it has been showed that their intersection with ω-regular languages is equivalent to co-Büchi.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we study temporal quality as well as the combinations of both aspects. One may try to reduce temporal quality to propositional quality by a repeated use of the X ("next") operator or by a use of bounded (prompt) eventualities [2,3]. Both approaches, however, partitions the future into finitely many zones and are limited: correctness of LTL is Boolean, and thus has inherent dichotomy between satisfaction and dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%